The Implementation of Green Accounting in Fish Canning Factories in Pengambengan Village, Jembrana Regency - Pipin Sephia; Titin Kartini; Tiara Tiara (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
This study explains the implementation of green accounting in Pengambengan Village, Jembrana Regency. This research is included in the type of descriptive research with a qualitative approach. The data collection techniques used include observation, interviews, and documents. The research subjects were determined based on the purposive sampling method and data analysis using Miles and Huberman. The results of the study showed that the classification of environmental costs carried out by the fish canning factory in Pengambengan Village, Jembrana Regency consisted of prevention costs, detection costs and internal failure costs. There is no external failure cost because the waste generated from the factory production process is not disposed of into the surrounding environment such as the beach but is processed by the company itself. The stages of environmental cost allocation consist of identification, recognition, measurement, presentation and disclosure.